Recovery Strategy For Bali Cattle Farms in The Area Affected By The Agung Mountain Eruption in Karangasem Regency - Liga, Lingga; Putri, B. R. T; Sumardani, N. L. G. (Jurnal Peternakan Tropika; Vol 7 No 2 (2019), 2019)
This research is intended to explore the recovery strategy of bali cattle farming business in the affected areas of Mount Agung eruption in Karangasem Regency. This research is expected to produce a renewal of the right strategy to be applied to the bali cattle breeding business in the affected areas of Mount Agung eruption in Karangasem Regency which is able to restore cattle farmer business and increase cattle farmers' income. This research was conducted in five sub-districts affected by the eruption of Mount Agung in Karangasem Regency, namely Rendang Regency, Selat, Kubu, Bebandem and Abang which were conducted from February to April 2019 using a survey method. The location of the study was determined by purposive sampling method. This research used 85 respondents consisting of 75 cattle farmers, 5 SIMANTRI companions, and 5 experts. The results of the IFE-EFE analysis indicate that the value of internal factors 2.54 and the value of external factors 2.34 which indicate the business position of Bali cattle farms in the areas affected by the eruption of Mount Agung are in quadrant V in the IE matrix, namely the defense and maintanance division. There are nine alternative strategies produced, namely 1) providing nonverbal information facilities in the form of flayer or banners regarding information on livestock shelter; 2) socializing to cattle farmers about how to handle livestock during eruptions; 3) forming small groups of cattle farmers in each village; 4) provide a location/place to hold a stock exchange; 5) conduct training in making backup bait; 6) conduct training in processing livestock waste; 7) provide capital for livestock bussines development throught bussines plan competition organized by the goverment; 8) the government provides transportation to transport livestock in areas affected by the eruption; 9) educating farmers to implement appropriate technology for livestock business. Keywords: Bali cattle, affected areas of eruption, recovery strategy